Potential of emodepside for vector-borne disease control - Pattarapon Khemrattrakool; Thitipong Hongsuwong; Theerawit Phanphoowong; Patchara Sriwichai; Kittiyod Poovorawan; Joel Tarning; Kevin C. Kobylinski (Malaria Journal)
Abstract Background Emodepside is an anthelmintic used in veterinary medicine that is currently under investigation in human clinical trials for the treatment of soil-transmitted helminths and possibly Onchocerca volvulus. Emodepside targets the calcium-activated voltage-gated potassium slowpoke 1 (SLO-1) channels of presynaptic nerves of pharynx and body wall muscle cells of nematodes leading to paralysis, reduced locomotion and egg laying, starvation, and death. Emodepside also has activity against Drosophila melanogaster SLO-1 channels. Orthologous SLO-1 genes are present in Anopheles gambiae and Aedes aegypti, suggesting that emodepside may have activity against mosquitoes. Methods Both Anopheles dirus and Ae. aegypti were blood-fed emodepside across a range of concentrations (1–10,000 nM) and mosquito survival was monitored for 10 days. Co-feeding experiments were also performed with An. dirus blood fed ivermectin at the concentrations that kills 25% (LC25) and 50% (LC50) of mosquitoes with and without emodepside at clinical peak concentration in humans (Cmax) and five times the Cmax, and mosquito survival was monitored for 10 days. Results Emodepside had weak mosquito-lethal effects in An. dirus but none observed in Ae. aegypti at the concentrations evaluated. The An. dirus emodepside LC50 was 4,623 [4,159–5,066] ng/ml which is > 100-fold greater than the peak concentrations seen in human. The ivermectin and emodepside co-feed experiment with An. dirus did not indicate any altered effect of ivermectin on mosquito survival when emodepside co-fed at human Cmax or five times that of the human Cmax. Conclusions Emodepside was not lethal to An. dirus at human-relevant concentrations and had no effect on Ae. aegypti survival. Thus, mass distribution of emodepside does not appear to be a potential tool for vector-borne disease control. Emodepside induced mortality in An. dirus does suggest that the SLO-1 channel could be a potential target for novel vector control and may warrant further investigation.